"Polypodium vulgare" subsp. "melitense" new subspecies from Gozo, Maltese Islands (Pteridophyta: "Polypodiaceae") - Peroni, Adalberto; Peroni, Gabriele; Mifsud, Stephen (Botanica Complutensis, 2013)
Polypodium vulgare L. subsp. melitense subsp. nov. from the island of Gozo (Malta) is described. Polypodium vulgares.l. is being recorded for the first time from Malta. Comparison of the new subspecies with other Polypodiumtaxa present in continental Europe and the Mediterranean area is outlined. Pteridophyta of the Maltese Islands are finally listed.
Keywords: Pteridophyta; Polypodiaceae; Polypodium vulgare new subspecies; Gozo; Malta